The information professional faced with scientific collaboration and Science 2.0 - Serrano-Cobos, Jorge; Orduña-Malea, Enrique; Robles-Crespo, Daniel (Anuario ThinkEPI, 2009)
The main task of a scientific documentation manager is to provide help and coverage to researchers, usually in two ways: scientific watch and visibility. The recent emergence and use of a range of technologies and trends (within the so-called Science 2.0) is helping to encourage and facilitate collaborative research between researchers in different universities and countries. This paper reviews some of these services, and reflects on possible effects of their use in scientific information production and consumption patterns.